A process for the preparation of low odor glass fiber reinforced nylon
Patent Information
- Application Number
- CN202610987251.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]针对现有尼龙材料气味刺激性强、挥发性有机化合物含量偏高,且现有制备技术除味效果有限、易对材料性能造成不利影响的技术问题,本发明的目的是提供一种低气味玻璃纤维增强尼龙的制备方法,通过优化原料组分配比、改进制备工艺路线,实现异味组分的高效去除,同时保障尼龙材料的力学性能及加工性能,满足高端应用领域的使用需求
1、除味效果显著:本发明通过引入改性疏水型气味吸附剂,并结合分步聚合(高压聚合+真空聚合)、真空脱挥、高温蒸汽萃取多重协同除味工艺,可高效去除尼龙材料中残留的单体、低聚物及助剂挥发物等异味组分,制得的低气味尼龙气味等级≤3.0级,VOC含量≤240μgC/g,显著优于现有普通尼龙材料,可满足汽车内饰、食品接触等高端领域对气味指标的严苛要求;
Smart Images

Figure CN122878743A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nylon material preparation technology, specifically to a method for preparing low-odor glass fiber reinforced nylon, which is particularly suitable for the preparation process of nylon products for automotive and household appliances that have strict requirements for odor performance and volatile emission indicators. Background Technology
[0002] Nylon (PA), also known as polyamide, is a class of engineering plastics with excellent comprehensive properties. It possesses good mechanical properties, wear resistance, solvent resistance, and oil resistance, and is widely used in various industrial fields such as automobiles, electronics, and machinery manufacturing. Among them, PA6, as one of the most widely used nylon varieties, has been extensively used in automotive interior parts, home appliance housings, and other products due to its excellent processing performance and low production cost.
[0003] However, existing nylon materials generally suffer from significant odor problems during preparation and processing, which severely limits their promotion in high-end applications. The odor of nylon materials mainly originates from three aspects: First, monomers (such as caprolactam in the preparation of PA6) and oligomers remaining from incomplete polymerization reactions; these substances are prone to volatilization during high-temperature processing or use, producing an irritating odor. Second, various additives added during processing (such as antioxidants, lubricants, compatibilizers, etc.); some of these additives are highly volatile and easily release unpleasant odors. Third, fillers such as glass fibers have poor compatibility with the nylon resin matrix, easily forming interface defects during processing, leading to the precipitation of low-molecular-weight substances from the interface, further exacerbating odor emission.
[0004] Currently, existing low-odor nylon preparation technologies mainly achieve odor control through two approaches: adding adsorbents or optimizing processing techniques. However, both have certain limitations: some technologies use ordinary activated carbon as an odor adsorbent, which is highly hydrophilic, easily affecting the mechanical properties and processing stability of nylon materials, and also has poor adsorption effect on hydrophobic odor components; some technologies only use a single vacuum devolatilization process for deodorization, which is difficult to completely remove residual monomers and oligomers in the material, resulting in limited deodorization effect; and some technologies have problems such as complex processes and high production costs, making them unsuitable for large-scale industrial production. For example, Chinese patent CN101314672A discloses a high-gloss, low-odor, reinforced nylon composite material and its preparation method. This method improves odor performance by adding components such as microbeads and zinc sulfide, but it only uses a simple mixing and granulation process, which is not ideal for removing residual monomers. Chinese patent CN111349336A uses carbon powder as an adsorbent. Although it can adsorb odors to a certain extent, the carbon powder has poor dispersibility and can easily have an adverse effect on the appearance and mechanical properties of nylon materials.
[0005] Therefore, developing a simple and cost-effective method for preparing low-odor nylon that can effectively remove odor components from nylon materials while ensuring their excellent mechanical and processing properties has become a pressing technical challenge in this field. Summary of the Invention
[0006] To address the technical problems of existing nylon materials having strong odor, high volatile organic compound content, and limited odor removal effect of existing preparation techniques, which can easily adversely affect material performance, the purpose of this invention is to provide a method for preparing low-odor glass fiber reinforced nylon. By optimizing the raw material composition ratio and improving the preparation process, the method achieves efficient removal of odor components while ensuring the mechanical and processing properties of the nylon material, thus meeting the needs of high-end applications.
[0007] Technical solution To achieve the above-mentioned objectives, the present invention provides a method for preparing low-odor glass fiber reinforced nylon, comprising the following steps: S1 Raw Material Pretreatment The nylon resin chips were subjected to vacuum drying, with the drying temperature controlled at 70-100℃ and the vacuum degree ≤1×10⁻⁶. 3 Pa, drying time 2-6h, to obtain dried nylon resin; Modified glass fiber is obtained by immersing glass fiber in an aminosilane coupling agent for 1-2 hours, followed by filtration and drying. Attapulgite clay and quaternary ammonium salt surfactant were mixed at a mass ratio of 100:5-10, and then successively activated, crushed and sieved to obtain a hydrophobic odor adsorbent. S2 Mixed Ingredients Based on the total mass of the formula, accurately weigh the following raw material components by mass percentage: 65-85% dried nylon resin, 0.5-3.5% hydrophobic odor adsorbent, 0.1-1% antioxidant, and 0.2-2% lubricant; put the above raw material components into a high-speed mixer and dry mix for 3-5 minutes at a speed of 1000-1500 r / min and a temperature of 60-80℃ to ensure that each component is uniformly dispersed and to obtain a mixed raw material; S3 stepwise polymerization Add the mixed raw materials to the polymerization reactor, add 5-8% deionized water by mass of the total formulation, seal the reactor, pressurize to 6-12 MPa, raise the temperature to 200-280℃, and react under constant temperature and pressure for 3-7 hours; then evacuate and depressurize to ≤1×10⁻⁶. 3 Pa, adjust the temperature to 160-220℃, maintain the temperature for 8-12 hours, and obtain nylon melt; S4 Extrusion Granulation Nylon melt is fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled at 220-295℃, the main extruder speed is 20-50Hz, and 15-25% modified glass fiber is added by side feeding. After the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for rapid cooling, then pelletized by a pelletizer, and finally screened by a vibrating screen to obtain nylon finished granules. S5 deodorization post-treatment The nylon particles were subjected to high-temperature steam extraction at 80-100℃ for 2-4 hours; subsequently, the nylon particles were placed in a vacuum oven and dried at a temperature of 80-100℃ and a vacuum degree ≤1×10⁻⁶. 3 Drying at 4-6 hours under Pa conditions removes moisture from nylon particles and volatile components remaining from the extraction process, yielding a low-odor nylon product.
[0008] In some embodiments, in S1, the nylon resin chips are PA6 chips with a relative viscosity of 2.50-2.80 and a water content of 0.1%-0.3%. PA6 chips within this parameter range have excellent processing performance and polymerization efficiency, and low residual monomer content, making them suitable for the preparation of low-odor nylon materials.
[0009] In some embodiments, in S1, the drying temperature is 80-100°C and the vacuum degree is ≤1×10⁻⁶. 3 Pa, drying time is 2-4 hours.
[0010] In some embodiments, in S1, the length of the modified glass fiber is 4.0±1.0 mm, and the aminosilane coupling agent is selected from one or more of KH550, KH560, and KH595; this length of glass fiber has the best reinforcing effect on nylon materials, and the selected aminosilane coupling agent can effectively improve the compatibility between glass fiber and nylon resin matrix, and can be flexibly selected according to actual processing requirements.
[0011] In some embodiments, during the preparation of the hydrophobic odor adsorbent in S1, the activation temperature is 80-300℃, such as 90℃, 100℃, 110℃, 120℃, 150℃, etc., the activation time is 1-6h, such as 2h, 4h, etc., and the sieve mesh size is 200-1250 mesh, such as 400 mesh, 600 mesh, 800 mesh, 1000 mesh. The activation treatment can significantly improve the specific surface area and adsorption performance of attapulgite, and the sieving treatment can ensure that the adsorbent particle size is uniform and ensure its dispersion performance in the nylon resin matrix.
[0012] In S1, the drying process effectively removes moisture from the nylon resin chips, preventing water from causing hydrolysis of the nylon molecular chains during subsequent polymerization and processing, which could lead to odor generation and a decline in material performance. The aminosilane coupling agent effectively improves the compatibility between glass fiber and the nylon resin matrix, reduces the generation of interface defects, lowers the amount of low-molecular-weight substances released, and enhances the reinforcing effect of glass fiber on nylon materials. After being modified by quaternary ammonium salt surfactants, attapulgite becomes hydrophobic, which can avoid adverse effects on the performance of nylon materials due to moisture adsorption. At the same time, it has a huge specific surface area and a special crystal structure, which can efficiently adsorb residual monomers, oligomers, and volatile additives in nylon materials, as well as odor components. Moreover, its excellent dispersion performance will not have a negative impact on the appearance and mechanical properties of nylon materials.
[0013] According to the present invention, nylon resin serves as the matrix material, providing the product with basic mechanical properties; the hydrophobic odor adsorbent is used to adsorb odor components in the material, and its addition amount must be strictly controlled to avoid excessive addition affecting material performance or insufficient addition leading to poor deodorization effect; the antioxidant can effectively inhibit the oxidative degradation reaction of nylon material during high-temperature processing, reducing the generation of odor components; the lubricant can improve the processing fluidity of nylon material, reduce frictional heat generation and material degradation during processing, and at the same time reduce the volatilization of the lubricant itself, reducing the unpleasant odor it brings.
[0014] In some embodiments, in S2, the antioxidant is a compound of pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and tris(2,4-di-tert-butylphenol) phosphite, with a mass ratio of 1:1. This compound antioxidant has a synergistic antioxidant effect, which can effectively inhibit the oxidative degradation reaction of nylon materials during high-temperature processing and use, and reduce the generation of odor components.
[0015] In some embodiments, in S2, the lubricant is an ultra-high molecular weight polysiloxane with a molecular weight of 4-8 million; this type of lubricant has excellent high temperature resistance and extremely low volatility, which can effectively improve the processing fluidity of nylon materials, while avoiding the generation of unpleasant odors through its own volatilization.
[0016] In some embodiments, in the S3 stepwise polymerization, in the first polymerization stage, the pressure is 8-10 MPa, the temperature is 220-240°C, and the reaction is carried out at a constant temperature and pressure for 4-6 hours; in the second polymerization stage, the pressure is reduced to 0.5-0.8 × 10⁻⁶ MPa under vacuum. 3 Pa, adjust the temperature to 170-190℃, and keep the reaction at that temperature for 8-10 hours.
[0017] According to the present invention, in the S3 stepwise polymerization, the first polymerization stage is a high-pressure polymerization stage, which can promote the full polymerization reaction of nylon resin and reduce the content of residual monomers; the second polymerization stage is a vacuum polymerization stage, which can further remove low molecular weight substances and residual monomers generated during the polymerization process, while promoting the cross-linking reaction of nylon molecular chains and improving the mechanical properties of the material; the vacuum environment can effectively prevent air from entering the reactor and causing oxidative degradation of nylon molecular chains, and reduce the generation of odor components.
[0018] According to the present invention, in S4, the vacuum pump can further remove volatile odor components from the nylon melt during the extrusion process, and the temperature gradient settings of each section are in line with the processing characteristics of PA6, which can avoid degradation reaction of the nylon melt and ensure the stability of the processing process.
[0019] In some embodiments, in S4, the temperatures of each section of the twin-screw extruder are specifically set as follows: Zone 1 230-250℃, Zone 2 240-260℃, Zone 3 240-260℃, Zone 4 230-250℃, Zones 5 to 8 220-240℃, and Zone 9 230-250℃. This temperature setting conforms to the processing characteristics of PA6, effectively preventing degradation reactions in the nylon melt and ensuring the stability of the processing and the consistency of product quality.
[0020] In some embodiments, in S4, the pelletizer rotates at a speed of 950-1200 r / min, and the vibrating screen has an aperture of 3-6 mm. This parameter setting ensures that the nylon pellets are of uniform size, while removing defective pellets by screening with a vibrating screen, thereby improving the consistency of product quality.
[0021] According to the present invention, in S5, the high-temperature steam in the extraction process can quickly dissolve and remove the volatile odor components remaining in the nylon particles, especially the residual monomers and oligomers.
[0022] In one specific embodiment, the method includes the following steps: S1 Raw Material Pretreatment: PA6 slices were vacuum dried, with the drying temperature controlled at 80℃ and the vacuum degree at 0.8×10⁻⁶. 3 Dry nylon resin was obtained by drying at 4 Pa for 4 hours; modified glass fiber was obtained by immersing glass fiber with a length of 4.0±1.0 mm in KH550 aminosilane coupling agent for 1 hour, and then filtered and dried; attapulgite clay was mixed with quaternary ammonium salt surfactant. Mix at a mass ratio of 100:5, where R1 is C 12 H 25 R2, R3, and R4 are methyl groups, and X is Cl. The mixture is activated at 80°C for 4 hours, pulverized, and passed through a 1250-mesh sieve to obtain a hydrophobic odor adsorbent. S2 Mixed Ingredients: Based on the total mass percentage of the formula, accurately weigh 77.5% of dry nylon resin, 2% of hydrophobic odor adsorbent, 0.3% of a 1:1 mass ratio of pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid) and tris(2,4-di-tert-butylphenol) phosphite compound, and 0.2% of polysiloxane with a molecular weight of 4 million; put the above raw material components into a high-speed mixer and dry mix for 5 minutes at a speed of 1000 r / min and a temperature of 60℃ to obtain the mixed raw material; S3 stepwise polymerization: The mixed raw materials are added to the polymerization reactor, along with 5% (by mass) of deionized water from the total formulation. The reactor is then sealed and pressurized to 10 MPa, heated to 240°C, and reacted under constant temperature and pressure for 6 hours. Subsequently, the pressure is reduced to 0.8 × 10⁻⁶ MPa by vacuum. 3 Pa, heat to 190℃, hold for 10 hours to obtain nylon melt; S4 Extrusion Granulation: Nylon melt is fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled as follows: Zone 1 250℃, Zone 2 250℃, Zone 3 240℃, Zone 4 230℃, Zones 5 to 8 220℃, Zone 9 230℃, and the main extruder speed is 30Hz; 15% modified glass fiber is added to the side feed. After the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for cooling, and then pelletized by a pelletizer at 950r / min. After screening by a vibrating screen to remove unqualified particles, nylon granules are obtained. S5 deodorization post-treatment: Nylon particles are subjected to high-temperature steam extraction at 80℃ for 4 hours, and then placed in a vacuum oven at 80℃ and a vacuum degree of 1×10⁻⁶. 3 The low-odor nylon product was obtained by drying under Pa conditions for 6 hours.
[0023] On the other hand, the present invention also provides a low-odor glass fiber reinforced nylon prepared by the above-described method, wherein the low-odor glass fiber reinforced nylon has an odor level ≤3.0, a VOC content ≤240μgC / g, a tensile strength ≥95MPa, and an impact strength ≥12kJ / m. 2 The odor level was tested according to GB / T 27630-2011 "Guidelines for Air Quality Evaluation in Passenger Cars", the VOC content was tested using thermal desorption-gas chromatography, and the mechanical properties were tested according to GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics - Part 1: General Rules" and GB / T 1043.1-2008 "Determination of Impact Strength of Simply Supported Beams of Plastics - Part 1: Non-Instrumental Impact Test".
[0024] Beneficial effects Compared with the prior art, the present invention has the following beneficial technical effects: 1. Significant deodorization effect: This invention introduces a modified hydrophobic odor adsorbent and combines a multi-synergistic deodorization process of stepwise polymerization (high-pressure polymerization + vacuum polymerization), vacuum devolatilization, and high-temperature steam extraction. This process can efficiently remove residual monomers, oligomers, and volatile additives from nylon materials, resulting in low-odor nylon with an odor level ≤3.0 and a VOC content ≤240μgC / g. This is significantly better than existing ordinary nylon materials and can meet the stringent requirements for odor indicators in high-end fields such as automotive interiors and food contact applications. 2. Excellent Mechanical Properties: This invention optimizes the raw material composition ratio, uses modified glass fiber for reinforcement, and strictly controls the amount and dispersion performance of the odor adsorbent. This effectively avoids the adverse effects of the deodorization process on the mechanical properties of the nylon material, resulting in low-odor nylon with a tensile strength ≥95MPa and an impact strength ≥12kJ / m. 2 It has excellent comprehensive mechanical properties; 3. Stable processing performance: The preparation process of this invention is simple and highly controllable. Through the pretreatment of raw materials and the optimization of process parameters, the adverse effects of factors such as moisture and oxidative degradation on the processing process are effectively avoided. The nylon melt has excellent fluidity and the extrusion granulation process is stable, making it suitable for large-scale industrial production. 4. Environmentally friendly and cost-controllable: The hydrophobic odor adsorbent used in this invention is prepared by modifying natural attapulgite clay. The raw materials are widely available, the production cost is low, and it is non-toxic and non-irritating, meeting environmental protection requirements. The entire preparation process does not require the addition of expensive equipment and reagents, the production cost is controllable, and it is easy to promote and apply. 5. Wide range of applications: The low-odor nylon produced by this invention has the characteristics of low odor, excellent mechanical properties and processing performance. It can be widely used in many fields such as automotive interior (such as dashboard, door panel, armrest), home appliance shell (such as refrigerator and washing machine shell), and food contact plastics (such as food packaging containers and tableware). It has broad market application prospects. Attached Figure Description
[0025] Figure 1 A schematic process flow diagram of the method according to the present invention is shown. Detailed Implementation
[0026] The present invention will be further described in detail below with reference to specific embodiments, but its protection scope is not limited by the following embodiments.
[0027] Unless otherwise specified, the raw materials and reagents used in the examples are all conventional and commercially available in the art; the methods and equipment used are all conventional methods and equipment in the art.
[0028] in, PA6: Purchased from Xinhui Meida Nylon Co., Ltd., M32800; Fiberglass: Purchased from Taishan Fiberglass Co., Ltd., ECS10-3.0-T435N; Aminosilane coupling agent: purchased from Jiangsu Chenguang Chemical Research Institute, KH550; Attapulgite: purchased from Anhui Mingmei Mineral Chemical Co., Ltd. Quaternary ammonium salt surfactants: purchased from Shandong Taiyuan Chemical Co., Ltd. Antioxidant: BASF (Irganox 1010 / 168); Preparation of PA6-G15: Weigh 84.8% of PA6 M32800, 0.1% of antioxidant Irganox1010, and 0.1% of antioxidant Irganox168 according to the formula, mix them at high speed to obtain mixed raw materials, and add 15% modified glass fiber for side feeding and extrusion pelleting.
[0029] Example 1 A method for preparing low-odor glass fiber reinforced nylon specifically includes the following steps: S1 raw material pretreatment: PA6 chips (relative viscosity 2.7, moisture content 0.25%) were vacuum dried, with the drying temperature controlled at 80℃ and the vacuum degree at 0.8×10⁻⁶. 3 Dry nylon resin was obtained by drying at Pa for 4 hours; modified glass fiber was obtained by immersing glass fiber with a length of 4.0±1.0 mm in KH550 aminosilane coupling agent for 1 hour, and then filtered and dried. S2 Mixed Ingredients: Based on the total mass percentage of the formula, accurately weigh 79.5% of dried nylon resin, 0.3% of antioxidant (a mixture of pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid) and tris(2,4-di-tert-butylphenol) phosphite in a mass ratio of 1:1), and 0.2% of lubricant (ultra-high molecular weight polysiloxane, molecular weight 4 million). Put all the above raw material components into a high-speed mixer and dry mix for 5 minutes at a speed of 1000 r / min and a temperature of 60℃ to obtain the mixed raw material. S3 stepwise polymerization: The mixed raw materials are added to the polymerization reactor, along with 5% (by mass) of deionized water from the total formulation. The reactor is then sealed and pressurized to 10 MPa, heated to 240°C, and reacted under constant temperature and pressure for 6 hours. Subsequently, the pressure is reduced to 0.8 × 10⁻⁶ MPa by vacuum. 3 Pa, adjust the temperature to 190℃, and maintain the reaction temperature for 10 hours to obtain nylon melt; S4 Extrusion Granulation: Nylon melt is fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled as follows: Zone 1 250℃, Zone 2 250℃, Zone 3 240℃, Zone 4 230℃, Zones 5 to 8 220℃, Zone 9 230℃, and the main extruder speed is 30Hz; 15% modified glass fiber is added to the side feed. After the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for cooling, and then pelletized by a pelletizer at 950r / min. After screening by a vibrating screen to remove unqualified particles, nylon granules are obtained. S5 deodorization post-treatment: Nylon particles are subjected to high-temperature steam extraction at 80℃ for 4 hours, and then placed in a vacuum oven at 80℃ and a vacuum degree of 1×10⁻⁶. 3 The low-odor nylon product was obtained by drying under Pa conditions for 6 hours.
[0030] Example 2 A method for preparing low-odor glass fiber reinforced nylon specifically includes the following steps: S1 raw material pretreatment: PA6 chips (relative viscosity 2.7, moisture content 0.25%) were vacuum dried, with the drying temperature controlled at 80℃ and the vacuum degree at 0.8×10⁻⁶. 3 Dry nylon resin was obtained by drying at 4 Pa for 4 hours; modified glass fiber was obtained by immersing glass fiber with a length of 4.0±1.0 mm in KH550 aminosilane coupling agent for 1 hour, and then filtered and dried; attapulgite clay was mixed with quaternary ammonium salt surfactant (structural formula...) R1 is C 12 H 25 R2, R3, and R4 are methyl groups, and X is Cl. They are mixed in a mass ratio of 100:5, activated at 80°C for 4 hours, pulverized, and passed through a 1250-mesh sieve to obtain a hydrophobic odor adsorbent. S2 Mixed Ingredients: Based on the total mass percentage of the formula, accurately weigh 82.5% of dry nylon resin, 2% of hydrophobic odor adsorbent, 0.3% of antioxidant (a mixture of pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid) and tris(2,4-di-tert-butylphenol) phosphite in a mass ratio of 1:1), and 0.2% of lubricant (ultra-high molecular weight polysiloxane, molecular weight 4 million). Put all the above raw material components into a high-speed mixer and dry mix for 5 minutes at a speed of 1000 r / min and a temperature of 60℃ to obtain the mixed raw material. S3 Extrusion Granulation: The mixed raw materials are fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled as follows: Zone 1 250℃, Zone 2 250℃, Zone 3 240℃, Zone 4 230℃, Zones 5 to 8 220℃, Zone 9 230℃, and the main machine speed is 30Hz; 15% modified glass fiber is added to the side feed; after the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for cooling, and then pelletized by a pelletizer at 950r / min. After the vibrating screen removes unqualified particles, nylon granules are obtained. S4 deodorization post-treatment: Nylon particles are subjected to high-temperature steam extraction at 80℃ for 4 hours, and then placed in a vacuum oven at 80℃ and a vacuum degree of 1×10⁻⁶. 3 Drying under Pa conditions for 6 hours yields a low-odor nylon product.
[0031] Example 3 A method for preparing low-odor glass fiber reinforced nylon specifically includes the following steps: S1 raw material pretreatment: PA6 chips (relative viscosity 2.7, moisture content 0.25%) were vacuum dried, with the drying temperature controlled at 80℃ and the vacuum degree at 0.8×10⁻⁶. 3 Dry nylon resin was obtained by drying at 4 Pa for 4 hours; modified glass fiber was obtained by immersing glass fiber with a length of 4.0±1.0 mm in KH550 aminosilane coupling agent for 1 hour, and then filtered and dried; attapulgite clay was mixed with quaternary ammonium salt surfactant (structural formula...) R1 is C 12 H 25 R2, R3, and R4 are methyl groups, and X is Cl. They are mixed in a mass ratio of 100:5, activated at 80°C for 4 hours, pulverized, and passed through a 1250-mesh sieve to obtain a hydrophobic odor adsorbent. S2 Mixed Ingredients: Based on the total mass percentage of the formula, accurately weigh 77.5% of dry nylon resin, 2% of hydrophobic odor adsorbent, 0.3% of antioxidant (a mixture of pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid) and tris(2,4-di-tert-butylphenol) phosphite in a mass ratio of 1:1), and 0.2% of lubricant (ultra-high molecular weight polysiloxane, molecular weight 4 million). Put all the above raw material components into a high-speed mixer and dry mix for 5 minutes at a speed of 1000 r / min and a temperature of 60℃ to obtain the mixed raw material. S3 stepwise polymerization: The mixed raw materials are added to the polymerization reactor, along with 5% (by mass) of deionized water from the total formulation. The reactor is then sealed and pressurized to 10 MPa, heated to 240°C, and reacted under constant temperature and pressure for 6 hours. Subsequently, the pressure is reduced to 0.8 × 10⁻⁶ MPa by vacuum. 3 Pa, heat to 190℃, hold for 10 hours to obtain nylon melt; S4 Extrusion Granulation: Nylon melt is fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled as follows: Zone 1 250℃, Zone 2 250℃, Zone 3 240℃, Zone 4 230℃, Zones 5 to 8 220℃, Zone 9 230℃, and the main extruder speed is 30Hz; 15% modified glass fiber is added to the side feed. After the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for cooling, and then pelletized by a pelletizer at 950r / min. After screening by a vibrating screen to remove unqualified particles, nylon granules are obtained. S5 deodorization post-treatment: Nylon particles are subjected to high-temperature steam extraction at 80℃ for 4 hours, and then placed in a vacuum oven at 80℃ and a vacuum degree of 1×10⁻⁶. 3 Drying under Pa conditions for 6 hours yields a low-odor nylon product.
[0032]
[0033] The present invention conducted a series of relevant performance tests on PA6-G15 prepared above and the products prepared in Examples 1-3, and the results are shown in the table below:
[0034] In Example 1, compared with PA6-G15, no hydrophobic odor adsorbent was added, a stepwise polymerization process was used, and the remaining steps and process parameters remained the same.
[0035] The nylon product obtained in Example 1 was subjected to performance testing. The test results are as follows: odor level 3.2, VOC content 320 μgC / g, tensile strength 104 MPa, and impact strength 12.5 kJ / m. 2 The test results show that, without the addition of hydrophobic odor adsorbents and using a stepwise polymerization process, the odor of the nylon material is significantly reduced compared to the conventional method, the VOC content is greatly reduced, and the deodorization effect is significantly improved.
[0036] In Example 2, compared with Example 1, a hydrophobic odor adsorbent was added, the stepwise polymerization process was not used, and the remaining steps and process parameters remained the same.
[0037] The nylon product obtained in Example 2 was subjected to performance testing. The test results are as follows: odor level 3.5, VOC content 380 μgC / g, tensile strength 101 MPa, and impact strength 11.2 kJ / m. 2 The test results show that when the stepwise polymerization process is not used, the residual monomers and oligomers in the nylon material cannot be effectively removed, resulting in poor deodorization and a decrease in mechanical properties.
[0038] In Example 3, compared with the conventional examples, a hydrophobic odor adsorbent was added, and a stepwise polymerization process was adopted, while the remaining steps and process parameters remained the same.
[0039] The nylon product obtained in Example 3 was subjected to performance testing. The test results are as follows: odor level 2.7, VOC content 240 μgC / g, tensile strength 102 MPa, and impact strength 12.3 kJ / m. 2 The test results show that when hydrophobic odor adsorbents and stepwise polymerization processes are used, residual monomers and oligomers in nylon materials are effectively removed, resulting in the best odor removal effect.
[0040] The test results of the above embodiments and comparative examples show that the present invention, by adding a modified hydrophobic odor adsorbent and combining it with a multi-synergistic deodorization process of stepwise polymerization, vacuum devolatilization, and high-temperature steam extraction, can significantly reduce the odor and VOC content of nylon materials, while effectively ensuring their excellent mechanical properties. This invention has significant technical advantages compared with the prior art.
[0041] The odor level detection described in this invention is conducted by an odor evaluation team composed of 5-7 professionally trained evaluators, who score the odor according to GB / T 27630-2011 "Guidelines for Evaluating Air Quality in Passenger Cars". Level 1 is no odor, Level 2 is a slight odor that does not affect use, Level 3 is a noticeable odor that is not pungent or unpleasant, and Level 3 and above are noticeable odors that do not meet the performance requirements of this invention.
[0042] The VOC content detection method described in this invention employs thermal desorption-gas chromatography. The specific detection steps are as follows: a certain mass of nylon sample is accurately weighed and placed in a thermal desorption instrument. The sample is desorbed at 200°C for 30 minutes. The volatile components after desorption are detected and analyzed by a gas chromatograph, and the VOC content (μgC / g) is calculated.
[0043] In this invention, the mechanical properties of tensile strength and notched impact strength are tested according to GB / T 1040.1-2018 "Determination of tensile properties of plastics - Part 1: General" and GB / T 1043.1-2008 "Determination of impact strength of simply supported plastic beams - Part 1: Non-instrumental impact test".
[0044] According to actual application requirements, the raw material composition ratio and process parameters of this invention can be appropriately adjusted. For example, if it is necessary to further improve the impact strength of nylon material, the amount of modified glass fiber can be appropriately increased; if it is necessary to further reduce the odor of the material, the amount of hydrophobic odor adsorbent can be appropriately increased or the high-temperature steam extraction time can be extended. Such adjustments are all within the protection scope of this invention.
Claims
1. A method for preparing low-odor glass fiber reinforced nylon, comprising the following steps: S1 Raw Material Pretreatment The nylon resin chips were subjected to vacuum drying, with the drying temperature controlled at 70-100℃ and the vacuum degree ≤1×10⁻⁶. 3 Pa, drying time 2-6h, to obtain dried nylon resin; Modified glass fiber is obtained by immersing glass fiber in an aminosilane coupling agent for 1-2 hours, followed by filtration and drying. Attapulgite clay and quaternary ammonium salt surfactant were mixed at a mass ratio of 100:5-10, and then successively activated, crushed and sieved to obtain a hydrophobic odor adsorbent. S2 Mixed Ingredients Based on the total mass of the formula, accurately weigh the following raw material components by mass percentage: 65-85% dried nylon resin, 0.5-3.5% hydrophobic odor adsorbent, 0.1-1% antioxidant, and 0.2-2% lubricant; put the above raw material components into a high-speed mixer and dry mix for 3-5 minutes at a speed of 1000-1500 r / min and a temperature of 60-80℃ to ensure that each component is uniformly dispersed and to obtain a mixed raw material; S3 stepwise polymerization Add the mixed raw materials to the polymerization reactor, add 5-8% deionized water by mass of the total formulation, seal the reactor, pressurize to 6-12 MPa, raise the temperature to 200-280℃, and react under constant temperature and pressure for 3-7 hours; then evacuate and depressurize to ≤1×10⁻⁶. 3 Pa, adjust the temperature to 160-220℃, maintain the temperature for 8-12 hours, and obtain nylon melt; S4 Extrusion Granulation Nylon melt is fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled at 220-295℃, the main extruder speed is 20-50Hz, and 15-25% modified glass fiber is added by side feeding. After the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for rapid cooling, then pelletized by a pelletizer, and finally screened by a vibrating screen to obtain nylon finished granules. S5 deodorization post-treatment The nylon particles were subjected to high-temperature steam extraction at 80-100℃ for 2-4 hours; subsequently, the nylon particles were placed in a vacuum oven and dried at a temperature of 80-100℃ and a vacuum degree ≤1×10⁻⁶. 3 Drying at 4-6 hours under Pa conditions removes moisture from nylon particles and volatile components remaining from the extraction process, yielding a low-odor nylon product.
2. The method according to claim 1, wherein, In S1, The nylon resin chips are PA6 chips with a relative viscosity of 2.50-2.80 and a moisture content of 0.1%-0.3%. The drying temperature is 80-100℃ and the vacuum degree is ≤1×10⁻⁶. 3 Pa, drying time is 2-4 hours; and / or The modified glass fiber has a length of 3-5 mm; The aminosilane coupling agent is selected from one or more of KH550, KH560, and KH595; In the preparation process of the hydrophobic odor adsorbent, the activation temperature is 80-300℃, the activation time is 1-6h, and the sieve mesh size is 200-1250 mesh.
3. The method according to claim 1, wherein, In S2, The antioxidant is a compound of pentaerythritol tetrakis(β-(3,5-ditert-butyl-4-hydroxyphenyl)propionate) and tris(2,4-di-tert-butylphenol) phosphite, with a mass ratio of 1:
1. The lubricant is an ultra-high molecular weight polysiloxane with a molecular weight of 4-8 million.
4. The method according to claim 1, wherein, In S3, In the first polymerization stage, the pressure is 8-10 MPa, the temperature is 220-240℃, and the reaction is carried out at a constant temperature and pressure for 4-6 hours; in the second polymerization stage, the pressure is reduced to 0.5-0.8 × 10⁻⁶ MPa under vacuum. 3 Pa, adjust the temperature to 170-190℃, and keep the reaction at that temperature for 8-10 hours.
5. The method according to any one of claims 1 to 4, wherein, In S4, The specific temperature settings for each section of the twin-screw extruder are as follows: Zone 1 230-250℃, Zone 2 240-260℃, Zone 3 240-260℃, Zone 4 230-250℃, Zones 5 to 8 220-240℃, and Zone 9 230-250℃. The pelletizer has a rotation speed of 950-1200 r / min, and the vibrating screen has an aperture of 3-6 mm.
6. The method according to claim 1, wherein, The method includes the following steps: S1 Raw Material Pretreatment: PA6 slices were vacuum dried, with the drying temperature controlled at 80℃ and the vacuum degree at 0.8×10⁻⁶. 3 Dry nylon resin was obtained by drying at 4 Pa for 4 hours; modified glass fiber was obtained by immersing glass fiber with a length of 4.0±1.0 mm in KH550 aminosilane coupling agent for 1 hour, and then filtered and dried; attapulgite clay was mixed with quaternary ammonium salt surfactant. Mix at a mass ratio of 100:5, where R1 is C 12 H 25 R2, R3, and R4 are methyl groups, and X is Cl. The mixture is activated at 80°C for 4 hours, pulverized, and passed through a 1250-mesh sieve to obtain a hydrophobic odor adsorbent. S2 Mixed Ingredients: Based on the total mass percentage of the formula, accurately weigh 77.5% of dry nylon resin, 2% of hydrophobic odor adsorbent, 0.3% of a 1:1 mass ratio of pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid) and tris(2,4-di-tert-butylphenol) phosphite compound, and 0.2% of polysiloxane with a molecular weight of 4 million; put the above raw material components into a high-speed mixer and dry mix for 5 minutes at a speed of 1000 r / min and a temperature of 60℃ to obtain the mixed raw material; S3 stepwise polymerization: The mixed raw materials are added to the polymerization reactor, along with 5% (by mass) of deionized water from the total formulation. The reactor is then sealed and pressurized to 10 MPa, heated to 240°C, and reacted under constant temperature and pressure for 6 hours. Subsequently, the pressure is reduced to 0.8 × 10⁻⁶ MPa by vacuum. 3 Pa, heat to 190℃, hold for 10 hours to obtain nylon melt; S4 Extrusion Granulation: Nylon melt is fed into a twin-screw extruder, the extruder vacuum pump is turned on, and the temperature of each section of the twin-screw extruder is controlled as follows: Zone 1 250℃, Zone 2 250℃, Zone 3 240℃, Zone 4 230℃, Zones 5 to 8 220℃, Zone 9 230℃, and the main extruder speed is 30Hz; 15-25% modified glass fiber is added to the side feed; after the nylon melt is extruded through the extrusion die, it is sent to a cooling water tank at 20-40℃ for cooling, and then pelletized by a pelletizer at 950r / min. After screening by a vibrating screen to remove unqualified particles, nylon granules are obtained. S5 deodorization post-treatment: Nylon particles are subjected to high-temperature steam extraction at 80℃ for 4 hours, and then placed in a vacuum oven at 80℃ and a vacuum degree of 1×10⁻⁶. 3 Drying under Pa conditions for 6 hours yields a low-odor nylon product.
7. A low-odor glass fiber reinforced nylon prepared by the method according to any one of claims 1 to 6, wherein the low-odor glass fiber reinforced nylon has an odor level ≤ 3.0, a VOC content ≤ 240 μgC / g, a tensile strength ≥ 95 MPa, and an impact strength ≥ 12 kJ / m. 2 .
Citation Information
Patent Citations
High-gloss, low-smell, reinforced nylon composite material and preparation method thereof
CN101314672A
Low-odor glass fiber reinforced nylon modified material and preparation method thereof
CN111349336A